Author Correction: Simultaneous molecular MRI of extracellular matrix collagen and inflammatory activity to predict abdominal aortic aneurysm rupture (Scientific Reports, (2020), 10, 1, (15206), 10.1038/s41598-020-71817-x) - Adams, Lisa C.; Brangsch, Julia; Reimann, Carolin; Kaufmann, Jan O.; Buchholz, Rebecca; Karst, Uwe; Botnar, Rene M.; Hamm, Bernd; Makowski, Marcus R. (Scientific Reports, 2021)
The original version of this Article omitted affiliations for Jan O. Kaufmann. The correct affiliations for Jan O. Kaufmann are listed below: Charité –Universitätsmedizin Berlin, corporate member of Freie Universität Berlin, Humboldt-Universität Zu Berlin, and Berlin Institute of Health, Charitéplatz 1, 10117, Berlin, Germany. Division 1.5 Protein Analysis, Federal Institute for Materials Research and Testing (BAM), Richard-Willstätter- Str. 11, 12489 Berlin, Germany. Department of Chemistry, Humboldt-Universität zu Berlin, Brook-Taylor-Str. 2, 12489 Berlin, Germany. This has now been corrected in the HTML and PDF versions of this Article.
CRIS-Team Scopus Importer:2023-03-08